2023
DOI: 10.1038/s41467-023-40916-4
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-producing bacteria promote barley rhizosheath formation

Feiyun Xu,
Hanpeng Liao,
Jinyong Yang
et al.

Abstract: The rhizosheath, or the layer of soil closely adhering to roots, can help plants to tolerate drought under moderate soil drying conditions. Rhizosheath formation is the result of poorly understood interactions between root exudates, microbes, and soil conditions. Here, we study the roles played by the soil microbiota in rhizosheath formation in barley (a dry crop). We show that barley rhizosheath formation is greater in acid soil than in alkaline soil, and inoculation with microbiota from acid soil enhances rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…PGPR can promote plant growth by directly secreting plant hormones or by influencing the hormone synthesis process of plants [5]. The production of IAA has been recognized as an important factor in direct plant growth-promoting abilities of rhizosphere bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPR can promote plant growth by directly secreting plant hormones or by influencing the hormone synthesis process of plants [5]. The production of IAA has been recognized as an important factor in direct plant growth-promoting abilities of rhizosphere bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…As the second genome of plants, the rhizosphere microbiome plays an important role in promoting plant growth and disease resistance [4]. In particular, plant growth-promoting rhizobacteria (PGPR), which can benefit plants by producing plant growth hormones [5], convert many plant-unavailable essential nutrients, such as nitrogen, phosphorous, zinc and iron, into available forms, synthesize antibiotics or enhance induced systemic resistance (ISR) to help plants against pathogenic bacteria and fungi [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two bacterial strains isolated from rhizosheath (Chryseobacterium culicis and Paenibacillus polymyxa) were found to affect rhizosheath development, which appeared to be directly related to the ability of Flavobacterium sp. and Chryseobacterium culicis to produce growth hormones, while barley root sheaths inoculated with auxin-mutant strains were significantly stunted [176]. Studies have shown that the metabolic synthesis of growth hormones in plants is affected by the concentration of growth hormone in the soil, which appears to be linked to the bacterial production of the hormone [177].…”
Section: Bacterial Hormones Indirectly Affect Phosphorus Uptake By Pl...mentioning
confidence: 99%
“…The amount of auxin that plant-associated Flavobacterium produces is about 4.88 μg/ml ( Lin et al, 2023 ). Flavobacterium species associated with plants might synthesize auxin through the tryptophan-dependent pathway rather than the tryptophan-independent pathway ( Tillmann et al, 2021 ; Tsavkelova et al, 2007 ; Xu et al, 2023 ; Wang et al, 2015 ). For example, Flavobacterium sp.…”
Section: Determinants Produced By Flavobacterium F...mentioning
confidence: 99%
“…For example, Flavobacterium sp. 11 showed tryptophan-dependent IAA production regulated by the indole-3-glycerol phosphate synthase gene ( trpC ), which converts 1-( o -ecarboxyphenylamino)-1-deoxyribulose-5-phosphate to indole-3-glycerol-phosphate ( Kagan et al, 2008 ; Xu et al, 2023 ). In addition to auxin, the treatment of Flavobacterium sp.…”
Section: Determinants Produced By Flavobacterium F...mentioning
confidence: 99%